Clinical Course of Asymptomatic Isolated Distal Deep Vein Thrombosis of the Leg: A Single-Institution Study - Shimabukuro, Nobuhiro (Ann Vasc Dis, 2019)
Background: The natural history of asymptomatic isolated distal deep vein thrombosis (DVT) of the leg is unclear. This study aimed to describe a 3-month and 1-year clinical course after diagnosis of asymptomatic isolated distal DVT of the leg. Methods: This study included 127 patients with asymptomatic, sonographically proven isolated distal DVT who did not receive anticoagulant therapy and were retrospectively evaluated at our hospital between May 2014 and September 2016. After 3 months and 1 year, the presence or absence of venous thromboembolism recurrence and extension of DVT toward proximal veins was sonographically confirmed. Results: At 3-month and 1-year follow-ups, 125 and 109 patients were observed, respectively. All patients showed no symptoms or findings suspecting venous thromboembolism recurrence during the observation period. However, 43 patients underwent repeat ultrasonic examination, and thrombus extension was confirmed in 2 patients. Conclusions: Asymptomatic isolated distal DVT of the leg showed good prognosis, and thus uniform anticoagulation therapy was considered unnecessary. (This is a translation of Jpn J Phlebol 2018; 29(3): 309–314.)